Praksis Pembelajaran Aktif Dalam Perspektif Islam Mata Kuliah Psikologi Pendidikan Bagi Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar Islam Dalam Implementasi Penerapan Teknologi Pembelajaran Tahun 2022 - Agus Retnanto; Bahtiar Firdiansyah (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to describe the praxis of active learning in the Islamic perspective of the Educational Psychology course with the application of educational technology with the dimensions of students and lecturers at IAIN Kudus, as well as describe the impact and accompanying the implementation of learning. This research with a qualitative approach is Class Action Research (CAR) by adopting the Kemmis and McTaggart stages in the form of planning, action, observation, and reflection. The social situation of this research includes Madrasah Ibtidaiyah (PGMI) Teacher Education students Class of 2020 with learning process activities. The data collection techniques used are observation, interviews, and questionnaires as triangulation. Active learning in the student dimension describes (a) the courage to express opinions, thoughts, feelings, and the courage to take part in lectures and assignments, (b) effort and creativity, freedom of innovation making exposure equipped with hyperlinks, interactive videos and individual learning games and group collaboration. Active learning in the lecturer dimension illustrates (a) efforts to foster and encourage students to increase enthusiasm, and participation by providing opportunities to function resources and creativity (b) carrying out functions and roles as innovators, motivators, and dynamic actors through e-learning, (c) inspiring actively exploring the sites and sources of knowledge needed, (d) providing opportunities for students to facilitate differences of opinion, (e) the ability to use a variety of strategies teaching and learning with a multimedia approach. The impact that describes the implementation of learning is the fundamentals of Islamic 5i (internalization, correction, substitution, addition, and fixation).